FAILURE MODE AND EFFECT ANALYSIS (FMEA) AS TREATMENT OF PREDICTIVE PREVENTION AND LEAKAGE OF BOILER TYPE BALANCE DRAF FAN - Muhammad Nurtanto; Ita Novita Sari; Sulaeman Deni Ramdani; Moh Fawaid (Universitas Sultan Ageng Tirtayasa, 2018)
Risk analysis aims to prevent the incompatibility of a system used in the testing process including the Boiler system. At the Labuan 2 Steam Power Plant (PLTU) 2, the Boiler component was declared